2019
DOI: 10.1016/j.cgh.2018.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Compared Abilities of Endoscopic Techniques to Increase Colon Adenoma Detection Rates: A Network Meta-analysis

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e146. Learning Objective-Upon completion of this activity, successful learners will be able to list the endoscopic techniques that have been shown to increase colon adenoma detection rate; list the endoscopic techniques that have been shown to increase mean adenoma per patient compared with standard colonoscopy; and list the endoscopic techniques that have not been shown to improve colon adenoma detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 89 publications
(6 reference statements)
2
63
0
1
Order By: Relevance
“…Further research is needed to assess the impact of distal colonoscope attachments on patient comfort, their role in tip stabilization to support effective polypectomy and whether the small increment in ADR at the higher end of the spectrum has any impact upon interval cancer rates and mortality. It further remains to be seen whether adjunct devices such as EAC or TAC (as compared with inexpensive measures such as NBI, longer withdrawal times, second look or retroflexion in the right colon or use of anti‐spasmodics) have a role in improving ADRs in day‐to‐day practice . Nevertheless head‐to‐head studies as presented here should be the new standard for novel device assessment in endoscopic clinical care.…”
Section: Published Parallel Group Randomized Controlled Trials Involvmentioning
confidence: 95%
See 1 more Smart Citation
“…Further research is needed to assess the impact of distal colonoscope attachments on patient comfort, their role in tip stabilization to support effective polypectomy and whether the small increment in ADR at the higher end of the spectrum has any impact upon interval cancer rates and mortality. It further remains to be seen whether adjunct devices such as EAC or TAC (as compared with inexpensive measures such as NBI, longer withdrawal times, second look or retroflexion in the right colon or use of anti‐spasmodics) have a role in improving ADRs in day‐to‐day practice . Nevertheless head‐to‐head studies as presented here should be the new standard for novel device assessment in endoscopic clinical care.…”
Section: Published Parallel Group Randomized Controlled Trials Involvmentioning
confidence: 95%
“…It further remains to be seen whether adjunct devices such as EAC or TAC (as compared with inexpensive measures such as NBI, longer withdrawal times, second look or retroflexion in the right colon or use of anti-spasmodics) have a role in improving ADRs in day-to-day practice. 8 Nevertheless head-to-head studies as presented here should be the new standard for novel device assessment in endoscopic clinical care.…”
mentioning
confidence: 96%
“…Perhaps this is a good time to consider adopting low-cost interventions to minimize risk of transmission of the Covid-19 virus, decrease the number of incomplete or low-quality procedures that require rescheduling, and minimize the need for anesthesia medication and support. Low-cost interventions have been proven effective [11].…”
Section: E986mentioning
confidence: 99%
“…Fuccio et al compared the WE, WI and ACI methods in a comparative meta-analysis and demonstrated the superiority of the WE method over both WI and ACI in terms of overall adenoma detection rate and right colon adenoma detection rate (RADR) [8]. Another network meta-analysis by Facciorusso et al supported the use of water techniques for improving overall ADR [9]. Critically, the authors of this study did not perform an analysis of the proximal adenoma detection rate (PADR).…”
Section: Introductionmentioning
confidence: 99%